Biological exposure indices of occupational exposure to benzene: A systematic review - Razzagh Rahimpoor; Hamed Jalilian; Heidar Mohammadi; Abdulrasoul Rahmani (Heliyon, 2023)
The current study aimed to systematically review the studies concerning the biological monitoring of benzene exposure in occupational settings. A systematic literature review was conducted in Scopus, EMBASE, Web of Science, and Medline from 1985 through July 2021. We included peer-reviewed original articles that investigated the association between occupational exposure to benzene and biological monitoring. We identified 4786 unique citations, of which 64 cross-sectional, one case-control, and one cohort study met our inclusion criteria. The most studied biomarkers were urinary trans-trans muconic acid, S- phenyl mercapturic acid, and urinary benzene, respectively. We found the airborne concentration of benzene as a key indicator for choosing a suitable biomarker. We suggest considering urinary benzene at low (0.5–5.0 TLV), urinary SPMA and TTMA at medium (5.0–25 and 25–50 TLV, respectively), and urinary phenol and hydroquinone and catechol at very high concentrations (500 and 1000 TLV ≤, respectively). Genetic polymorphism of glutathione S-transferase and oral intake of sorbic acid have confounding effects on the level of U-SPMA and U-TTMA, respectively. The airborne concentration, smoking habit, oral consumption of sorbic acid, and genetic polymorphism of workers should be considered in order to choose the appropriate indicator for biological monitoring of benzene exposure.